Existence and Uniqueness of Solutions for Fuzzy Mixed Type of Delay Differential Equations - Bharathi, D. Prasantha; Jayakumar, T.; Muthukumar, T.; Vinoth, S. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we are defining the fuzzy type of mixed delay differential equations. The necessity of studying the mixed delay differential equation in terms of fuzzy is that the single real valued solution can be ordered as the set of fuzzy valued solution. So it is very important in establishing the existence of solution for the fuzzy mixed type of delay differential equations using necessary theorems and lemmas. In addition we are also proving that the existing solution is unique.